2012
DOI: 10.1007/s00068-012-0186-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain and its impact on quality of life following a traumatic rib fracture

Abstract: This study confirms the high incidence of chronic pain after a traumatic rib fracture. While the majority of the patients can manage this pain without interference of their quality of life, a few do suffer from life style/work interference and may have to resort to regular analgesic usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 13 publications
2
34
0
Order By: Relevance
“…One small retrospective investigation of rib fracture patients in a trauma registry (102 patients) found no specific risk factors of chronic pain beyond 12 months. However, the differences from our results could be explained by study population dissimilarities (the majority of patients in the trauma registry study had other concomitant injuries; those patients were excluded from our cohort to isolate the effect of MTI), by its small sample size, and by its retrospective study design (no systematic evaluation or follow‐up) . Another small study (80 patients) focused on pain as a secondary outcome (the primary outcome was to compare the analgesic effect of tramadol to nonsteroidal anti‐inflammatory drugs) .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…One small retrospective investigation of rib fracture patients in a trauma registry (102 patients) found no specific risk factors of chronic pain beyond 12 months. However, the differences from our results could be explained by study population dissimilarities (the majority of patients in the trauma registry study had other concomitant injuries; those patients were excluded from our cohort to isolate the effect of MTI), by its small sample size, and by its retrospective study design (no systematic evaluation or follow‐up) . Another small study (80 patients) focused on pain as a secondary outcome (the primary outcome was to compare the analgesic effect of tramadol to nonsteroidal anti‐inflammatory drugs) .…”
Section: Discussionmentioning
confidence: 78%
“…Up to 90% of MTI patients will seek medical attention within 72 hours of trauma . MTI can produce significant pain that can last for several months . This thoracic pain, often severe at the time of the trauma, can significantly limit the ability to work and to perform daily activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pain may cause strong distressing sensation whereas local discomfort meant as an unpleasant or abnormal sensitivity to touch by CPT. There are studies reported that all trauma patients with acute pain upon discharge should receive a routine practice of prescribed analgesic, which may cause poor restricted movement, and inability to breath and participate in normal activities [39,40,41]. In the current study, all patients who were encouraged to carry out physiotherapy practice up to 6 months, they were taking the prescribed oral analgesics post discharge and immediate pre CPT.…”
Section: Discussionmentioning
confidence: 88%
“…However, much lower prevalence has also been reported in the literature. According to Gordy et al [32], the prevalence of CP assessed by the McGill Pain Questionnaire at 6 months of trauma was 22%. It was 22.5% in a Singapore study enrolling 102 patients with rib fractures [33].…”
Section: Discussionmentioning
confidence: 99%